Effectiveness of Telehealth on Treatment Adherence of Mental Patients - Lina Darmayanti Bainuan; Nuniek Setyo Wardani; Intan Parulian Tiurma Roosleyn; Arnindya Kanti Prasasti; Sondang Tio Helena Manurung (CV. Get Press Indonesia, 2026)
Mental disorders are a global health concern requiring long-term therapy, yet treatment adherence remains low, often leading to relapse and rehospitalization. The advancement of telehealth offers opportunities to enhance continuous patient monitoring and support. However, evidence regarding its effectiveness in Indonesia is still limited. This study aimed to analyze the effectiveness of telehealth in improving treatment adherence among patients with mental disorders. A pre-experimental design with a one-group pretest-posttest approach was used. The study was conducted at Dr. Soeharto Heerdjan Psychiatric Hospital, Jakarta, from July to September 2025. A total of 30 respondents were selected using purposive sampling based on inclusion criteria. The telehealth intervention was implemented for 8 weeks and included scheduled online consultations, medication reminder systems, and family education. Treatment adherence was measured using the Medication Adherence Rating Scale (MARS), and data were analyzed using a paired t-test with a significance level of 0.05. The results showed a significant increase in the mean adherence score from 5.9 ± 1.3 before the intervention to 8.4 ± 1.1 after the intervention (p=0.000). This indicates that telehealth significantly improved treatment adherence. In conclusion, telehealth can be recommended as an effective strategy to support outpatient care and improve adherence among patients with mental disorders.